The clinical significance of computer capillaroscopy for differential diagnosis of the respiratory tract diseases in children - Yu. L. Mizernitsky (Rossijskij Vestnik Perinatologii i Pediatrii, 2020)
Computerized capillaroscopy of the nail bed is a non-invasive and most accessible method for studying microcirculation parameters in children; it is effectively used in a wide variety of pediatric pathologies. However, there are only few studies in this promising direction in children with acute and chronic bronchopulmonary diseases.Objective. To evaluate the morpho-functional features of capillary blood flow in children with the respiratory system diseases of infectious and allergic genesis and to evaluate their clinical significance.Materials and method. 238 children aged from 2 to 17 years with acute and chronic respiratory diseases were examined in the in-patient and outpatient hospitals. Along with traditional clinical methods all patients underwent computerized capillaroscopy of the nail bed to assess the morphological and functional state of the microvasculature.Results. Children with allergic diseases of the respiratory tract are characterized not only by pronounced structural changes in the capillaries in the form of weak differentiation at the level of capillaries of the third tier, but also by functional disorders of the capillary bed. They include a change in the parameters of all parts of the capillary and a marked increase in the length of the perivascular zone, interconnected with the activity level of chronic allergic inflammation. These changes were most pronounced in patients with bronchial asthma. The patients with infectious diseases of the respiratory system are characterized by a change in microcirculation parameters predominantly in the venous section of the capillaries, they are more pronounced in patients with lower respiratory tract diseases rather than with upper respiratory tract diseases.Conclusion. Structural and morpho-functional changes in microcirculation revealed by computerized nail capillaroscopy of the nail bed can be used as additional differential diagnostic criteria in the algorithms for the diagnosis of allergic diseases of the respiratory tract, which will contribute to the early detection of this pathology and timely therapy.